Pharmacokinetic disposition of cefotaxime in buffalo calves (Bubalus bubalis) following single intramuscular administration - SHARMA, S K; SRIVASTAVA, A K; DEORE, M D (The Indian Journal of Animal Sciences, 2014)
The pharmacokinetic disposition of cefotaxime was investigated in buffalo calves following its single intramuscular administration (10 mg.kg-1). The peak plasma concentration ofcefotaxime at 20 min was 11.3±0.4S µg.ml-1 which declined to 0.068±0.03 µg.ml-1 at 7 hr. The absorption half-life and elimination half-life were 0.145±0.047 and 1.24±0.07 hr respectively. The apparent volume of distribution and total body clearance were 1.17±0. 10L.kg-1 and 0.67±0.09 L.kg-1 hr respectively. Approximately 3.5% of the total administered drug was recovered in urine within 24 hr of its administration. An appropriate intramuscular dosage regimen for cefotaxime in buffalo calves would be 11 mg/kg repeated at 8 hr intervals.